To assess the thermoregulation of neonates in the postnatal wards of the hospital: A prospective study - Kalengada, Prarthana Karumbaiah; Mangalgi, Sharanabasavesha; Pradeep, G C M (Indian Journal of Child Health, 2016)
Introduction: Hypothermia is a major cause of neonatal morbidity and mortality. Objective: To know the frequency of hypothermia in the postnatal wards and to know the relation of gestation and birth weight with the temperature of the neonates. Materials and Methods: Rectal temperature of 420 consecutive neonates shifted to postnatal wards of the hospital was measured. The gestation and birth weight of the neonates were recorded. The details were entered, and association of temperature to the birth weight and gestation was calculated. Results: About 70% of the neonates showed mild hypothermia. Gestation and weight of the neonates showed no significant association. Conclusion: The study shows the need to have more vigorous efforts to maintain the temperature in all the neonates in the postnatal wards.